Modified fibrin hydrogel for sustained delivery of RNAi lipopolyplexes in skeletal muscle. (13th December 2022) - Ngarande, Ellen; Doubell, Emma; Tamgue, Ousman; Mano, Manuel; Human, Paul; Giacca, Mauro; Davies, Neil Hamer
Abstract: RNA interference is a promising therapeutical approach presently hindered by delivery concerns such as rapid RNA degradation and targeting of individual tissues. Injectable hydrogels are one potentially simple and direct route towards overcoming these barriers. Here we report on the utility of a combination of a mildly modified form of the clinically utilised fibrin hydrogel with Invivofectamine ® 3.0, a lipid nonviral transfection vector, for local and sustained release. PEGylation of fibrin allowed for controlled release of small interfering RNA (siRNA)-lipopolyplexes for at least 10 days and greatly increased the stability of fibrin in vitro and in vivo . A 3D cell culture model and a release study showed transfection efficacy of siRNA-lipopolyplexes was retained for a minimum of 7 days. Injection in conjunction with PEGylated-fibrinogen significantly increased retention of siRNA-lipopolyplexes in mouse skeletal muscle and enhanced knockdown of myostatin mRNA that correlated with muscle growth. Thus, the increased efficacy observed here for the combination of a lipid nanoparticle, the only type of nonviral vector approved for the clinic, with fibrin, might allow for more rapid translation of injectable hydrogel-based RNA interference. Graphical abstract: